2019
DOI: 10.21315/aamj2019.24.s1.13
|View full text |Cite
|
Sign up to set email alerts
|

Network Competence and Firm Performance: The Mediating Role of Entrepreneurial Innovativeness Among Malaysian Chinese Entrepreneurs of Wholesale Businesses

Abstract: Entrepreneurial innovativeness has been considered as one of the crucial factors for any firm to achieve its superior performances. The aim of this paper is to analyse the mediating effect of entrepreneurial innovativeness in the relationship between network competence and firm performances including financial performance, non-financial performance, and business growth. Data were collected from 150 Malaysian Chinese wholesalers from the states of Selangor and Kuala Lumpur. Non-probability sampling technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Thus, H1 in this study can be accepted. This finding supports the findings of Miller (2015) and Sajilan and Tehseen (2019) (Eggers, Kraus, Hughes, Laraway, & Snycerski, 2013).…”
Section: Validity and Reliability Testingsupporting
confidence: 92%
“…Thus, H1 in this study can be accepted. This finding supports the findings of Miller (2015) and Sajilan and Tehseen (2019) (Eggers, Kraus, Hughes, Laraway, & Snycerski, 2013).…”
Section: Validity and Reliability Testingsupporting
confidence: 92%
“…To obtain information related to the research objectives, data were collected from SMEs in Malaysia. As the SMEs sector dominates most of the businesses in this country (Sajilan and Tehseen, 2019), the SMEs have become the striking force in the transformation process of the country toward "developed" country status (Abu and Mansor, 2019;Halim et al, 2015). But, with respect to innovation capability, the rank of Malaysia among other countries in the world (positioned 30th out of 140 countries) is relatively low (World Economic Forum, 2020), which might hinder the country's effort to move toward the knowledge-based and innovation-driven advanced economy (Arshad et al, 2018;Mamun, 2018).…”
Section: Research Settingmentioning
confidence: 99%
“…In addition, Hameed et al(2018) mentioned that in the SMEs sector of Malaysia, the implementation of innovative strategy is still in its infancy stage. In fact, SMEs in the service sector of Malaysia are more susceptible to the open innovation practices (Sajilan and Tehseen, 2019). Moreover, lower level of open innovation practices hinders the performance of SMEs in Malaysia and their competitiveness both in domestic and international level (Hameed et al, 2018).…”
Section: Research Settingmentioning
confidence: 99%
“…However, the direct relationship between network competence and firm performance suggested by Ritter and Gemünden (2003) and Ritter et al (2002) was not confirmed. A possible explanation for the absence of this direct link may be the fact that the network competence by itself is not sufficient to ensure a better performance, as was also found by Sajilan and Tehseen (2019) in the context of Malaysian Chinese firms. In line with the study of Pinho and Prange (2016), whose results show that social network relationships have strong impact on firm performance whenever dynamic capabilities are in place; our study demonstrates that network competence can help the development of those capabilities, which can contribute directly to improve firm performance.…”
Section: Discussionmentioning
confidence: 96%